2022
DOI: 10.1111/gcbb.12994
|View full text |Cite
|
Sign up to set email alerts
|

Implications of large‐scale miscanthus cultivation in water protection areas: A Life Cycle Assessment with model coupling for improved policy support

Abstract: Two major global challenges related to agriculture are climate change and the unbalanced nitrogen cycle. For both, national and international reduction targets have been defined to catalyse policy support for more sustainable farming systems. Miscanthus cultivation in water protection areas has been proposed as a contribution to achieving these targets. However, a thorough understanding of the underlying system dynamics at various spatial levels is required before recommendations for policy development can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Yield ranges shown typical for miscanthus cultivation in Southwest Germany were taken from own field trials (Weik et al, 2022). These are complemented with estimates on typical soil carbon sequestration associated with the cultivation of miscanthus on arable land.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield ranges shown typical for miscanthus cultivation in Southwest Germany were taken from own field trials (Weik et al, 2022). These are complemented with estimates on typical soil carbon sequestration associated with the cultivation of miscanthus on arable land.…”
Section: Methodsmentioning
confidence: 99%
“…Field emissions, including that is nitrous oxide, nitrate and phosphorus as well as heavy metals were modeled as suggested in Zampori and Pant (2019). Yield ranges shown typical for miscanthus cultivation in Southwest Germany were taken from own field trials (Weik et al, 2022). These are complemented with estimates on typical soil carbon sequestration associated with the cultivation of miscanthus on arable land.…”
Section: Primary Biomass Productionmentioning
confidence: 99%
“…Crop diversity, plant diversity Land/water/nutrient use efficiency Potential contribution of the BA Miscanthus mitigates leaching of nitrate to groundwater because it is deep rooting [ 239,240] and nitrogen fertilizer is generally unnecessary, except on soils of low fertility. N 2 O emissions from unfertilized miscanthus can be five times lower than from annual crops and up to 100 times lower than from intensive pasture.…”
Section: Nutrient Surplusmentioning
confidence: 99%
“…During the establishment phase, no significant difference was observed in N leaching between maize and miscanthus, but when mature, miscanthus decreased N leaching by 42% under fertilized conditions (224 kg N ha −1 ) and 82% when unfertilized (Studt et al., 2021). These characteristics make it a useful crop to include in water protection areas and as part of flood mitigation strategies, provided the variety used has a very low invasiveness risk to prevent escape along water courses (2.4) (Agostini et al., 2021; Ferrarini et al., 2017; Weik et al., 2022).…”
Section: What Are the Main Ecosystem Service Impacts To Be Considered...mentioning
confidence: 99%
“…While larger field sizes lead to greater economies of scale, it has been shown that smaller plantations of less than 1 ha can provide reasonable gross margins and make use of 5 m wide buffer zones besides water courses where fertilizer applications are prohibited (Winkler et al., 2020). Strategically situating miscanthus stands or planting in strips has been suggested as a useful mechanism to help buffer against nutrient runoff and soil erosion (Agostini et al., 2015; Anejionu & Woods, 2019; Weik et al., 2022).…”
Section: The Benefits Challenges and Trade‐offs Of Upscaling Miscanth...mentioning
confidence: 99%